Antioxidant and antimicrobial properties of Isodon amethystoides (Benth.) CY Wu et Hsuan leaf extracts against agriculturally important pathogenic fungi. Issue 1 (1st January 2019) - Zhao, Fenglan; Zhang, Wanjun; Meng, Xue; Yang, Xue; Yang, Lianzhi; Teng, Jingtong; Xue, Jianping; Duan, Yongbo; Sheng, Wei
Abstract: In this study, we investigated the antioxidant and antimicrobial activities of Isodon amethystoides (Benth.) CY Wu et Hsuan leaf extracts. Leaves were subjected to extraction with acetone, chloroform, ethanol and ethyl acetate. The extraction efficiency of these four solvents ranked as follows: acetone > chloroform > ethanol > ethyl acetate; highest extraction yield of 18.27% was obtained using acetone as the solvent. Total phenolic content and flavonoid content were determined using Folin–Ciocalteau and aluminium chloride (AlCl3 ) methods, respectively. The acetone extract had the highest total phenolic content (146.77 mg GAE/g dry extract) and flavonoid content (81.57 mg RE/g dry extract) among the four types of extracts. Further, the antioxidant activity was determined by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) method and the antimicrobial activity was evaluated using disc-diffusion and broth microdilution assay. The strongest antioxidant activity was observed in the acetone extract with a half minimal inhibitory concentration ( IC 50 ) of 0.4024 mg/mL in the DPPH scavenging assay. The acetone and ethyl acetate extracts exhibited strong antimicrobial activity. The strongest antibacterial activity of the acetone extract was observed against Bacillus subtilis and Escherichia coli with a minimum inhibitory concentration (MIC) of 0.10 mg/mL and 0.05 mg/mL, respectively. The acetone extract had high antifungal activity against three of the six agriculturally important pathogenic fungi with MIC ranging from 0.5 mg/mL to 0.8 mg/mL. The antioxidant and antimicrobial activities may be attributed to the high total phenolic and flavonoid contents in the acetone extract. Our findings suggest I. amethystoides leaves as an important source of natural compounds with potential use in agriculture.